L ANALYSE DES ASPECTS CULTURELS FRANÃAIS DANS LES EXTRAITS DU FILM FRANÃAIS, LES ACCORDS AUX THÃMES ET SON APPLICATION AU LYCÃE - Tricahyaningtyas, Yulia; Handayani, Sri; Syaefudin, Mohamad (Didacticofrancia: Journal Didactique du FLE, 2016)
The objective of this research is to describe French cultural aspects in French films, to classifyFrench cultural aspects and segments of French films in six themes, and to propose a lessonplans using the segments of French films. It is a descriptive qualitative research. Data source isthree French films: Ãtre et Avoir; Paris, Je Tâaime; and Yâaura tâil de la neige Ã  NoÃ«l?. Thosedatas are printscreen of French films segments and also the dialogue conversation sentences.I used a documentation methode to collect data. The result shows that it has found 65 segments of French films which contain the French cultural aspects. Those segments are based onCECRL theories about French cultural. Thereâs also 86 French cultural aspects within the segments, and 89 compatibilities which related from segments to the six themes of French subject.In high school, it can be used into French cultural learning.